Optimal sensorless adaptive optics schemes for super-resolution microscopy - Burke, D; Kenny, F; Patton, B; Booth, M (Optical Society of America, 2013)
Aberrations frequently affect the performance of microscopes. Superresolution microscopes, which combine optical and photo-physical phenomena to resolve below the diffraction limit, are more sensitive to aberrations.We develop adaptive schemes for aberration compensation in these systems. © OSA 2013.